Improved control strategy for fixed-speed compressors in parallel system. (May 2017) - Jung, Jaeheum; Lee, Won Je; Park, Sangmin; Kim, Younghun; Lee, Chul-Jin; Han, Chonghun
Highlights: This study suggested a practical control structure for parallel compressor system. This study improved an existing control structure used in industrial application. The improved control structure enables desired load sharing control. The improved control structure enables immediate anti-surge control. Abstract: Control systems for parallel compressor trains consist of a discharge pressure, anti-surge and load-sharing regulation. Control of a parallel compressor system has proven to be challenging because the control targets usually exhibit control interactions between the different control loops. To decouple this control interference, Mitsubishi Heavy Industries has developed an advanced feed-forward control structure for parallel fixed-speed compressor systems. However, operation in the presence of an unpredictable disturbance presents a few technical challenges for this structure. Most of these problems result in poor load sharing and then operation in the recycle mode in order to protect the system from surge conditions. Moreover, an anti-surge control delay occurs when operating under a low load. To overcome these problems, an improved control structure that incorporates an additional discharge flow controller signal and a nonlinear signal calculator for anti-surge valve control is proposed. To demonstrate the benefits of the proposed method, the control performance of the conventional control structure is compared to that of the proposed control structure. The target process is a parallel fixed-speed compressor system for a fuel gas supply plant. The improved control structure allows for desired load-sharing control, which is not possible with the conventional control structure. The improved control structure manages to exit the anti-surge control region, whereas the conventional control structure activates the interlock system.